Pengaruh Kompos TKKS, Jerami Padi dan Pupuk NPK terhadap Pertumbuhan dan Produksi Tanaman Cabai (Capsicum annuum L.) - Hapsoh; Leyna, Zulfa; Murniati (Jurnal Hortikultura Indonesia, 2019)
This study aims to determine the effect of compost and NPK fertilizer on the growth and production of chili pepper and get the best combination of treatments. This research was conducted at the University of Experimental Riau Agriculture Faculty of Garden from September 2017 to February 2018. This study used a randomized block design (RBD). The first factor was compost consisting of 3 levels: without compost, compost TKKS and rice straw compost. The second factor is NPK 16:16:16 fertilizer consisting of 3 levels: 0 kg ha-1, 125 kg ha-1 and 250 kg ha-1. Parameters observed were initial soil analysis, plant height, dichotomous height, crown width, flowering age, harvest age, fruit length, number of fruits per plant, fruit weight per plant and fruit weight per plot. Based on the results of the study it was found that the best treatment was application of rice straw compost 5 ton ha-1 and 125 kg ha-1 NPK fertilizer (½ recommended dosage).Keywords: C-organic, Dichotomous height, Fruit weight, Inceptisol